Analisis Penerimaan Teknologi Mobile Banking Pada Nasabah Wanita Karir Di Bank Rakyat Indonesia Cabang Ciputat - Tri Handayani; Husnayetti Husnayetti (Indonesian Journal of Economics Application (IJEA), 2019)
This study aims to analyze influence of perceived usefulness, ease to use and perceived risk availability of the use of mobile banking PT. Bank Rakyat Indonesia (Persero) Tbk. This study focused on mobile banking as part of banking. The technique of data collection is in the form of a questionnaire containing statements from 19 indicators with the amount of sample is 100 respondents. The analytical method is used multiple linear regression analysis. These results indicate the perceived usefulness show significant effect on using of mobile banking with the value 0.004 < 0.05. Ease to use with the value 0.000 < 0.05 show the significant impact of using a mobile banking. Perceived risk has significant effect on using mobile banking with the significan value 0.038 < 0.05.